2020
DOI: 10.1001/jamaoto.2019.4864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Associated With Internal Carotid Injury in Expanded Endoscopic Endonasal Skull Base Surgery

Abstract: to the internal carotid artery (ICA) during endoscopic endonasal skull base surgery does not typically occur as an isolated circumstance but often is the result of multiple factors.OBJECTIVE To assess the factors associated with ICA injury in an effort to reduce its occurrence. DESIGN, SETTING, AND PARTICIPANTSThis quality improvement study used a multicenter root cause analysis of ICA injuries sustained during endoscopic endonasal skull base surgery performed at 11 tertiary care centers across 4 continents (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 35 publications
(60 reference statements)
0
56
0
Order By: Relevance
“…An international multi‐institutional retrospective study was performed of cases of ICA injury during endoscopic endonasal skull base surgery not treated with embolization, stenting, or ligation. This is a follow up study to the previously reported ICA injury root cause analysis 17 . This study underwent Institutional Review Board review and approval.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…An international multi‐institutional retrospective study was performed of cases of ICA injury during endoscopic endonasal skull base surgery not treated with embolization, stenting, or ligation. This is a follow up study to the previously reported ICA injury root cause analysis 17 . This study underwent Institutional Review Board review and approval.…”
Section: Methodsmentioning
confidence: 97%
“…Lack of experience may also contribute to ICA injury and a greater risk has been suggested earlier in the learning curve prior to achieving proficiency 16 . A recent international multi‐institutional root cause analysis of 28 cases of ICA injury found that these cases are typically characterized by more than one risk factor and the study provided a case‐by‐case event description and recommendations 17 …”
Section: Introductionmentioning
confidence: 98%
“…While the indications and contraindications to surgery for sinonasal tumours have considerably evolved throughout the last decades, abutment, encasement, and frank invasion of the ICA have been invariably considered as a major criterion of difficult, dangerous, or even impossible resectability. Intraoperative rupture of the ICA has been reported to occur in 28/7160 (0.4%) endoscopic procedures and its consequences ranges from death to non-lethal cerebrovascular events, pseudoaneurysm, carotid-cavernous fistula, and need for vascular occlusion 45,46 . Although one could hypothesize that vessels-encroaching tumours should be referred to radiation oncologists, vascular toxicity actually represents a major concern even in patients undergoing RT that can considerably limit dose delivery in areas neighboring the vessel (Fig.…”
Section: Measures Against Major Vascular Complicationsmentioning
confidence: 99%
“…Tolerance can be evaluated through a combination of several techniques including clinical assessment, cross flow tim- ing, evoked potentials, and functional imaging. In patients demonstrating adequate cross flow from the contralateral vascular system, the decision on whether or not to perform endovascular ICA occlusion prior to surgery should be based on the estimated risk of intraoperative rupture, which has a known lethality of roughly 7-15% 46,47 , and possible need for vessel removal as part of the resection 48 . However, preoperative endovascular ICA occlusion should not be indicated carelessly, as the long-term effects of the procedure are unknown.…”
Section: Measures Against Major Vascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation